2020
DOI: 10.1039/c9sc04786g
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and transport of sulfate using macrocyclic squaramide receptors

Abstract: Lipophilic macrocycles efficiently extract sulfate ions from water into chloroform and transport this ion across a bulk liquid membrane in the presence of competing anions (chloride, nitrate and dihydrogenphosphate).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 51 publications
3
65
1
Order By: Relevance
“…10h However, because it uses an anion receptor as a transporter, this process and all those reported so far in the literature required the assistance of lipophilic counterion. 10 We envisioned that by using receptor 2 it would be possible to eliminate this drawback, and for the first time, transport sulfates in the form of alkali metal salts across a membrane. For comparative purposes, we investigated the U-tube transport experiments with both scenarios where the aqueous source phase contained a 50 mM solution of TBA 2 SO 4 or K 2 SO 4 and the bulk chloroform phase contained 5 mM receptor 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…10h However, because it uses an anion receptor as a transporter, this process and all those reported so far in the literature required the assistance of lipophilic counterion. 10 We envisioned that by using receptor 2 it would be possible to eliminate this drawback, and for the first time, transport sulfates in the form of alkali metal salts across a membrane. For comparative purposes, we investigated the U-tube transport experiments with both scenarios where the aqueous source phase contained a 50 mM solution of TBA 2 SO 4 or K 2 SO 4 and the bulk chloroform phase contained 5 mM receptor 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The group of these compounds mainly includes anion receptors: macrocyclic calix[ n ]pyrroles, TREN-based hexaurea, diiminoguanidine, and more recently macrocyclic squaramide derivatives. 10 Some of these receptors were found to recognize sulfate salts in unusual manner via contact ion pair interactions. 11 However, this approach requires the assistance of lipophilic counterions during the extraction or transport processes.…”
Section: Introductionmentioning
confidence: 99%
“…. 12 -selective receptors 11 and 12 (Figure 1) and found that the more lipophilic receptor (12) -free receptor by the addition of Ba(NO 3 ) 2 . Macrocycle 12 could also transport SO 4 2À through a bulk chloroform membrane via anion exchange under conditions simulating nuclear waste, demonstrating its potential to application in nuclear-waste treatment.…”
Section: àmentioning
confidence: 96%
“…Three trends can be distinguished in research on the synthesis of such systems. A first approach uses macrocyclic anion receptors with a properly designed binding cavity for a tetrahedral sulfate anion [ 12 , 13 , 14 ]. The second approach involves designing acyclic receptors capable of forming stable complexes with sulfate anions through self-organization [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%